Using physical, behavioral, and demographic variables to explain suite-level energy use in multiresidential buildings. (July 2015) - Brown, Craig; Gorgolewski, Mark; Goodwill, Alasdair
Abstract: Highly glazed high-rise residential towers are becoming increasingly popular across Canada, especially in Toronto. The present study explores energy use trends in these buildings, investigating the extent to which physical, behavioral, and demographic variables explain suite-level energy and water consumption. The study relies on data collected in four recently built towers, in Ontario, Canada, and involves submeter data from participating suites, questionnaire responses, and physical data relating to the each suite (e.g., exterior wall area). The average suite-level energy use intensity was found to be 125.6 ekWh/m 2 /year (not including heating, cooling and lighting for common spaces). The average end-use breakdown is 35% for electricity (plug loads and lighting), 34% for hot water, 20% for heating, and 11% for cooling. Energy use intensity differed by a factor of 7 between similar suites, electricity by a factor of 5, hot water by a factor of 13, cooling by a factor of 47, and heating by a factor of 67. Results suggest that occupant behavior and demographics account for 57% of the heating variability, 84% of the cooling variability, and 60% of electricity variability. For hot water, 51% of variability was explained by self-reported behaviors, with the rest of the variability being explained by behaviors which were not measured. Combining quantitative and qualitative datasets was an effective approach to understanding energy use in this understudied building type. Highlights: Studied LEED condo suites use 27% less energy than the Ontario average. Energy and water use varied widely between similar suites, as much as 67 times. Occupant behavior accounts for between 60 and 86% of consumption variability.